2005
DOI: 10.1590/s0102-695x2005000400020
|View full text |Cite
|
Sign up to set email alerts
|

Review of the plants with anti-inflammatory activity studied in Brazil

Abstract: ABSTRACT:The infl ammatory reaction is a response of the organism against an injury and it involves the action of complex events and mediators through of the blood vessels. The present work is a literature survey of the extracts of plants with anti-infl ammatory activity studied in Brazil. The review refers to 75 plants with their families, parts used, type of extract used, bioassay models and their activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
36

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 9 publications
1
63
0
36
Order By: Relevance
“…Estudos relatam a ação profi lática do óleo dos frutos de P. pubescens sobre Schistossoma mansoni em camundongos, sendo esta atividade atribuída ao 14,15-diidroxigeranilgeraniol (Demuner et al, 1996) e, atividade antiinfl amatória (Falcão et al, 2005). Os constituintes característicos deste táxon genérico são diterpenos lineares e tetracíclicos, apresentando esqueletos vinhaticano ou vouacapano (Campos et al, 1994a).…”
Section: Introductionunclassified
“…Estudos relatam a ação profi lática do óleo dos frutos de P. pubescens sobre Schistossoma mansoni em camundongos, sendo esta atividade atribuída ao 14,15-diidroxigeranilgeraniol (Demuner et al, 1996) e, atividade antiinfl amatória (Falcão et al, 2005). Os constituintes característicos deste táxon genérico são diterpenos lineares e tetracíclicos, apresentando esqueletos vinhaticano ou vouacapano (Campos et al, 1994a).…”
Section: Introductionunclassified
“…ovarian neoplasias (Silva et al, 2003), as inhibitors of HMG CoA reductase (Gonçalves et al, 2000), central analgesic activity (Almeida et al, 2001), employed in prevention of osteoporosis (Pereira et al, 2002), for the treatment of Parkinson's disease (Morais, 2003), with antileishmanial (Rocha et al, 2005, hypoglycemic (Barbosa-Filho et al, 2005), antiinfl ammatory activity (Falcão et al, 2005, Barbosa-Filho et al, 2006a and inhibitors of the enzyme acetylcholinesterase (BarbosaFilho et al, 2006b).…”
Section: Mechanism Of Anti-hypertensive Effect Based On the Inhibitiomentioning
confidence: 99%
“…Different approaches used to analyze the anti-infl ammatory potential of plant and plant-derived compounds have been developed in the past years (Mascolo, 1987;Alcaraz;Jiménez, 1988;Handa et al, 1992;Gorzalczany et al, 1996, Falcão et al, 2005. In this work we review specially the alkaloids isolated and identifi ed from the plants, previously demonstrated to have an anti-infl ammatory activity.…”
Section: Introductionmentioning
confidence: 97%